Optimalisasi Artificial Intelligent (AI) untuk Meningkatkan Minat Belajar Siswa Berkebutuhan Khusus di Sekolah Luar Biasa (SLB) Negeri Meulaboh - Dian Kristanti; Nursiah Nursiah; Mulyadi Mulyadi (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2026)
The low learning interest of students with special needs remains a major challenge in inclusive education. This condition is further compounded by the limited skills of teachers in implementing differentiated learning and utilizing Artificial Intelligence (AI). This community service activity aims to enhance teachers' skills in differentiated learning and AI utilization to foster the learning interest of students with special needs, while also providing innovative learning media relevant to their needs. The activity was conducted from July to November 2025 at SLB Negeri Meulaboh, involving 25 teachers through counseling and education, training, and mentoring methods. The materials covered an understanding of learning interest, differentiated learning strategies, and the application of AI in adaptive learning. The results indicated a 25% increase in teachers' understanding of learning interest and differentiated learning, a 50% improvement in teachers' skills in utilizing AI, and a 25% increase in the learning interest of students with special needs. The innovative learning media produced also proved effective in supporting a learning process better suited to students' individual characteristics. This activity successfully demonstrated that strengthening teachers' skills through AI and differentiated learning has a meaningful impact on improving the learning interest of students with special needs.